1988
DOI: 10.1083/jcb.106.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Purification and biosynthesis of a derepressible periplasmic arylsulfatase from Chlamydomonas reinhardtii.

Abstract: Abstract. The unicellular green alga Chlamydomonas reinhardtii responds to sulfate deprivation by producing an arylsulfatase (Lien, T., and O. Schreiner. 1975. Biochim. Biophys. Acta. 384:168-179; Schreiner, O., 1975. Biochim. Biophys. Acta. 384:180-193) and by developing the capacity to transport sulfate more rapidly (our unpublished data). The arylsulfatase activity, detectable 3 h after the transfer of the cells to low sulfate medium (~<10 IxM sulfate), is a periplasmic protein released into the culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 34 publications
1
77
1
3
Order By: Relevance
“…The results showed that although levels of chloroplast RNAs (cpRNAs) remained mainly unchanged under normal conditions, removal of S from the medium resulted in a decrease of 20-90% within 4-8 h and a decrease of 40-60% after 24 h. This decrease was reversible, and transcript abundance recovered to at or above the prestarvation levels after 2 h of S replenishment. This result contrasts with the accumulation of the nuclear ARS1 transcript, which is known to be induced under ϪS conditions (12). As shown in Fig.…”
Section: Abundance Of Several Chloroplast Mrnas Decreases Rapidly Undcontrasting
confidence: 50%
“…The results showed that although levels of chloroplast RNAs (cpRNAs) remained mainly unchanged under normal conditions, removal of S from the medium resulted in a decrease of 20-90% within 4-8 h and a decrease of 40-60% after 24 h. This decrease was reversible, and transcript abundance recovered to at or above the prestarvation levels after 2 h of S replenishment. This result contrasts with the accumulation of the nuclear ARS1 transcript, which is known to be induced under ϪS conditions (12). As shown in Fig.…”
Section: Abundance Of Several Chloroplast Mrnas Decreases Rapidly Undcontrasting
confidence: 50%
“…Cells were grown on solid medium for 4-5 days and the color reactions were allowed to develop for 20-24 hr before the cells were washed from the surface of the medium with deionized water to allow examination of the colored precipitate embedded in the medium. Liquid assays for alkaline phosphatase and arylsulfatase activities were performed as described previously (Lein and Schreiner 1975;de Hostos et al 1988;Quisel et al 1996).…”
Section: Methodsmentioning
confidence: 99%
“…P and S limitation elicit qualitatively similar effects on growth and photosynthesis, differing only in that the responses to S starvation occur more quickly following exposure of cells to medium devoid of S. General responses to nutrient limitation that have been analyzed include the cessation of growth at low cell densities Zhang et al 2002) and a reduction in photosynthetic O 2 evolution, which is mostly a consequence of reduced photosystem II (PS II) 1 activity (Wykoff et al 1998). The specific S-deprivation responses include an elevated rate of extracellular SO 4 2À uptake , secretion of extracellular arylsulfatases (Lein and Schreiner 1975;de Hostos et al 1988), and an increased cellular capacity to assimilate SO 4 2À by increasing levels of enzymes required for cysteine biosynthesis (Ravina et al 2002). Mechanisms for conserving S during limiting conditions include the rapid turnover of sulfolipids and their replacement with phospholipids (Sugimoto et al 2007(Sugimoto et al , 2008, the synthesis of putative cell wall proteins with a very low abundance of S-containing amino acids , and a potential change in the polypeptide composition of light harvesting complexes, favoring the synthesis of complexes with polypeptides containing low levels of sulfur amino acid (Nguyen et al 2008).…”
Section: àmentioning
confidence: 99%
“…Processes induced by S deprivation in this alga include rapid changes in cell size (Zhang et al, 2002), elevated production of hydrolytic extracellular enzymes (de Hostos et al, 1988;Takahashi et al, 2001), alterations in cell wall structure (Takahashi et al, 2001), changes in the activities and composition of the photosynthetic apparatus (Collier and Grossman, 1992;Wykoff et al, 1998;Zhang et al, 2004;González-Ballester et al, 2010;Cakmak et al, 2012aCakmak et al, , 2012bAksoy et al, 2013), scavenging of S from intracellular structures/molecules, elevated SO 4 22 transport activity Pootakham et al, 2010), and the synthesis of enzymes required for efficient S assimilation (Ravina et al, 1999(Ravina et al, , 2002González-Ballester et al, 2010). Moreover, S-depleted Chlamydomonas cells have been used for microarrayand RNA-seq-based transcript abundance studies (Zhang et al, 2004;Nguyen et al, 2008;González-Ballester et al, 2010), determination of metabolite profiles (Bölling and Fiehn, 2005), and the production of H 2 (Ghirardi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%